Exploring the impact of genetic factors and fatty acid quality on visceral and overall Fat levels in overweight and obese women: a genetic risk score study - Niloufar Rasaei; Atefeh Tavakoli; Saba Mohammadpour; Mehdi Karimi; Alireza Khadem; Azam Mohamadi; Seyedeh Fatemeh Fatemi; Fatemeh Gholami; Khadijeh Mirzaei (BMC Nutrition)
Abstract Background Recent studies suggest a link between dietary fat quality and obesity. Genetic risk scores (GRS) can predict obesity risk based on genetic factors. This study investigates how GRS and fatty acid quality affect visceral adiposity index (VAI) and body adiposity index (BAI) in overweight and obese women. Methods In this study, 278 overweight and obese women (aged 18–58) participated. We have used a comprehensive food frequency questionnaire (FFQ) to evaluate dietary intake and the fatty acids quality indexes. We have employed standard methods to measure biochemical factors, anthropometrics, and physical activity levels. Finally, the GRS was created by combining three SNPs [CAV-1 (rs3807992), Cry-1 (rs2287161), and MC4R (rs17782313)]. Results The study found that there was no significant association between the quality of fat intake (as measured by CSI score and N6/N3 score) and VAI or BAI in both crude (B = 70.70, SE = 35.14, CI:1.81-139.55, P = 0.04) and adjusted models (B = 93.67, SE = 39.28, CI:16.68–17.68, P = 0.01). CSI provides information on cholesterol and saturated fats. However, there was a notable interaction between the GRS and the N6/N3 score on VAI, suggesting that obese women with high obesity-related SNPs who consumed foods with a higher ratio of N6/N3 fatty acids tended to have an increased VAI. Conclusion This study shows; that eating more food sources containing a higher ratio of N6/N3 may be the reason for the increase in VAI in obese women who have high obesity-related SNPs and emphasizes the matter of personalized nutrition in obesity issues.